Intergenerational Learning and Social Capital in Choba Urban Indigenous Community in Port Harcourt Nigeria (Global Journal of Human-Social Science, 2019)
This paper examines intergenerational learning an informal aspect of adult learning in an indigenous community. Intergenerational learning involves older people and young people where both are teachers and learners in a shared learning process. The study examines the pattern of intergenerational learning in urban indigenous community. What informed the conduct of this study is the increase intergeneration gap and perhaps the individualistic lifestyle that characterized urban indigenous communities. The study was carried out in Choba an urban settlement in Port Harcourt. To collect data, we conducted Focus Group Discussion and key personality interview in the study area. The findings reveal that intergenerational learning is reciprocal and empowering and can be used to foster social capital and social cohesion. It also shows that the three forms of intergenerational learning are applicable in the urban indigenous communities. These forms are transferred learning, transactional learning, and transformational learning.
Keywords: indigenous; intergenerational; learning; traditional adults; social capital